2020
DOI: 10.1111/petr.13946
|View full text |Cite
|
Sign up to set email alerts
|

Declining mortality rates in children admitted to ICU following HCT

Abstract: HCT may cure malignant and benign hematologic diseases as well as severe immunodeficiencies in children. Though HCT is beneficial to many patients, HCT patients risk severe and life-threatening toxicities, infections, and immunological dysregulation as aGvHD, cGvHD, VOD, TAM, BO, BOOP, and PVOD/SOS. 1,2 Respiratory complications are the most frequent causes leading to ICU admittance. 1 Historically, the prognosis of pediatric HCT patients requiring intensive care is poor. In the late 90s, mortality rates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…Sixty-four manuscripts met search criteria and 24 were included as primary reports of pediatric HCT patients who underwent ECLS. These 24 reports included 11 single case reports (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), four single institution case series (28)(29)(30)(31), two multi-institution case series (32,33), and seven registry reports from Extracorporeal Life Support Organization (ELSO), Pediatric Heath Information System (PHIS), and Virtual Pediatric Systems (VPS) (14,15,(34)(35)(36)(37)(38). As patients included in these case reports, series, and registries are variably deidentified, we cannot exclude the possibility of patient overlap in these multiple manuscript formats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty-four manuscripts met search criteria and 24 were included as primary reports of pediatric HCT patients who underwent ECLS. These 24 reports included 11 single case reports (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), four single institution case series (28)(29)(30)(31), two multi-institution case series (32,33), and seven registry reports from Extracorporeal Life Support Organization (ELSO), Pediatric Heath Information System (PHIS), and Virtual Pediatric Systems (VPS) (14,15,(34)(35)(36)(37)(38). As patients included in these case reports, series, and registries are variably deidentified, we cannot exclude the possibility of patient overlap in these multiple manuscript formats.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to obtain more detailed patient information, six single- and multi-institutional case series have been reviewed. Jensen et al (30) reported a cohort of n = 4 pediatric HCT patients treated with ECLS between 2000 and 2017 with three of the four surviving to hospital discharge. In 2021, Potratz et al (31) and Bridges et al (32) each reported an additional n = 9 children, of whom n = 3 and n = 2 survived, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1 Advances in HCT have led to expanding indications and eligibility, with good overall survival and disease-free outcomes. [2][3][4][5] Immune effector cell therapies-for example, chimeric antigen receptor T-cells directed against antigens such as CD-19-have been associated with remarkable remission rates of more than 90% among patients with relapsed or refractory acute lymphoblastic leukaemia, who previously had no other curative options. [6][7][8] Nonetheless, 10-40% of children receiving these therapies might require support in the paediatric intensive care unit (PICU).…”
Section: Introductionmentioning
confidence: 99%
“…HCT, and neonatal and paediatric immune effector cell therapies (appendix p 1). Panelists were selected from eight diverse disciplines and the membership and leadership of: (1) the Extracorporeal Life Support Organization (ELSO); (2) Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) Network (HCT and cancer immuno therapy subgroup); (3) the Pediatric Diseases Working Party of the European Society for Blood and Marrow Transplantation (EBMT); (4) the supportive care committee of the Pediatric Transplantation and Cellular Therapy Consortium (PTCTC); and (5) the Pediatric Intensive Care Oncology Kids in Europe Research (POKER) group of the European Society of Pediatric and Neonatal Intensive Care (ESPNIC). Recom mendations were developed via a Quaker-based consensus technique (figure 1), 28,29 and prepared according to the Appraisal of Guidelines, Research and Evaluation reporting checklist (see appendix for more details).…”
Section: Introductionmentioning
confidence: 99%
“…With decreasing mortality rate among PICU patients (1), there are growing reports of a significant proportion of survivors developing symptoms of anxiety, depression, and post-traumatic stress disorder (PTSD) following their ICU admission (2, 3). This phenomenon is similarly observed in parents of both PICU (4, 5) and neonatal ICU (NICU) survivors (6–8).…”
mentioning
confidence: 99%